From traditional livestock exchange to modern trade systems: The transformation of Dayak economic practices - Pelipa, Emilia Dewiwati; Marganingsih, Anna; Bobi, Yopinus; Astikawati, Yunita (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2025)
This study explores the transformation of the Dayak Desa livestock trading system in Sintang Regency, West Kalimantan, from a traditional barter-based exchange to a modern market-oriented economy. Historically, economic life in the Dayak Desa community was embedded within cultural norms and social relations, reflecting Polanyi’s (2014) concept of the embedded economy. Barter served as the dominant system, with livestock such as pigs and chickens functioning both as food sources and social capital. The renti—a local, body-based measurement unit—was used to determine the value and size of pigs, representing an indigenous knowledge system transmitted through generations. Using a qualitative ethnographic-historical approach, the study draws upon interviews, participant observation, and documentation involving customary leaders and traders. Findings reveal that barter practices reflected social reciprocity rather than profit motives, while the gradual integration of money introduced a hybrid economic system combining traditional and market logics. The conversion of renti to metric kilograms (1 renti ≈ 15–40 kg) illustrates the community’s adaptive response to market modernization while retaining cultural integrity. The persistence of traditional valuation mechanisms signifies the resilience of indigenous economic institutions amid external economic pressures. The study concludes that the Dayak Desa trade system embodies a form of institutional layering, balancing customary governance with modern efficiency. It emphasizes the need to document, preserve, and integrate traditional measurement systems into contemporary market practices to ensure sustainable, culturally grounded economic development. By aligning indigenous economic heritage with modernization, the Dayak Desa community demonstrates that cultural continuity and economic progress can coexist harmoniously